Pressing needle therapy combined with Chinese herbal medicine ointment massage and nursing of a patient with abdominal distension caused by chronic gastritis of liver-gallbladder damp-heat syndrome (揿针联合中药膏摩治疗1例脾胃湿热证胃痞病腹胀患者的护理体会) - WANG Qian (王倩); ZHANG Cheng (张程); QI Huan (祁欢); XU Bing (许冰) (中西医结合护理)
This article summarizes the experience of using pressing needle therapy combined with Chinese herbal medicine ointment massage to improve abdominal distension in patients with abdominal distension caused by chronic gastritis of liver-gallbladder damp-heat syndrome. The article determines the methods of Traditional Chinese Medicine nursing techniques, which includes pressing needle therapy to unblock meridians and regulate Qi; Chinese herbal ointment massage to combine medicine and massage techniques to stimulate the Qi of the gastrointestinal meridians and mobilize the positive energy in the body to alleviate abdominal discomfort symptoms. In addition, comprehensive nursing interventions such as dietary guidance, daily living care and psychological nursing were carried out to relieve the clinical symptoms and improve the sleep quality of the patient. (本文总结1例揿针联合中药膏摩改善脾胃湿热胃痞病腹胀患者的护理经验。基于护理评估和中医辨证, 开展揿针联合中药膏摩中医适宜技术, 揿针疏通经络, 调理气机; 中药膏摩使药物和手法相融合, 激发胃肠经络元气, 调动体内正气, 减轻腹部不适症状。同时配合饮食指导、生活起居及心理疏导等常规护理, 有效改善患者腹胀症状, 提高患者睡眠质量。)